Effects of vitamin E-diffused highly cross-linked UHMWPE particles on inflammation, apoptosis and immune response against S. aureus. (October 2017) - Chen, Weishen; Bichara, David A.; Suhardi, Jeremy; Sheng, Puyi; Muratoglu, Orhun K.
Abstract: Particle-induced osteolysis and periprosthetic joint infection (PJI) are closely associated with periprosthetic tissue immune function. The objective of this study was to determine the effects of polyethylene particles on inflammation and response against S. aureus . Effects that vitamin E-diffused cross-linked UHMWPE (VE-PE) particles had on apoptosis, inflammation, and bactericidal activities compared to virgin cross-linked UHMWPE (control PE) particles were examined. Murine RAW 264.7 macrophages exposed to VE-PE particles in vitro were less apoptotic, secreted less tumor necrosis factor (TNF)-α, and responded more effectively against lipopolysaccharide or S. aureus compared to control PE particles. Implantation of VE-PE particles in murine calvaria in vivo caused less reactive oxygen species generation, less apoptosis, and less osteolysis compared to control PE particles. Implantation of PE particles in mice calvaria for 28 days, followed by inoculation with S. aureus in the same site where PE particles were implanted, demonstrated enhanced S. aureus clearance in the VE-PE group at day 33 after inoculation. These findings indicate that VE-PE particles might be less inflammatory and might preserve innate immunity of local tissue, allowing for enhanced clearance of bacteria.